15 peintres de ma génération - Pollac, Jean (Paris : Galerie Ariel, 1964)
Messagier ; Appel ; Tabuchi ; Corneille ; Mihailovitch ; Pouget ; Doucet ; Gillet ; Riopelle ; Lindstrom ; Marfaing ; REbeyrolle ; Alechinsky ; Maryan ; Bitran
15 peintres de ma génération, Galerie Ariel, Paris, novembre - décembre 1964
boek